Incidence and Characteristics of Neonatal Herpes: Comparison of Two Population-Based Data Sources, New York City, 2006–2015. Issue 2 (February 2019) - Lao, Steven; Flagg, Elaine W.; Schillinger, Julia A.
Abstract : Background: Neonatal herpes (nHSV) is a potentially fatal disease caused by herpes simplex virus (HSV) infection during the neonatal period. Neonatal herpes simplex virus infections are not nationally notifiable, and varying incidence rates have been reported. Beginning in 2006, New York City (NYC) required reporting of nHSV infections and conducted case investigations. We compared the use of administrative hospital data with active surveillance to monitor trends in nHSV infection. Methods: We compared the incidence and characteristics of nHSV cases as measured using population-based surveillance and administrative hospital discharge data collected between 2006 and 2015. Surveillance cases were defined as laboratory-confirmed HSV infections in NYC-resident infants aged 60 days or younger at diagnosis. Administrative cases were defined as NYC-resident infants aged 60 days or younger at hospital admission whose records included an HSV diagnosis. Neonatal herpes cases after ritual Jewish circumcision with direct orogenital suction were excluded. Results: There were 107 surveillance cases (9.9 per 100, 000 live births) and 131 administrative cases (12.1 per 100, 000 live births). Incidence was highest in infants born to non-Hispanic black mothers aged 20 years or younger (surveillance, 57.2 per 100, 000 live births; administrative data, 31.2 per 100, 000 live births). The distribution of cases by year did not significantly differ across data sources. Surveillance cases had a higher case-fatality rate (18.7%) compared with administrative cases (8.4%; P = 0.019). Conclusions: Administrative hospital data can be used to measure the incidence of nHSV infection and describe disease burden across population subgroups in jurisdictions where nHSV reporting is not required. However, administrative data may underascertain nHSV case fatality. Abstract : This study compares the incidence and characteristics of neonatal herpes simplex virus infection measured using 2 different population-based data sources.Supplemental digital content is available in the text.